Study of the effect of compounds of transition elements on the micellar catalysis of strength formation of reactive powder concrete - Shishkin, Alexsander (Eastern-European Journal of Enterprise Technologies, 2016)
Changes in the rate of cement hydration affect the rate of concrete compressive strength formation. Under certain conditions, an increase in the cement hydration rate improves the concrete compressive strength. This is especially true for reactive powder concretes. The paper studies the effect of micellar solutions, consisting of a mixture of a micelle-forming surfactant and compounds of transition elements. A feature of the study was investigating the simultaneous effect of micelle-forming surfactants and compounds of transition elements on the change in the concrete strength. The study found that given micellar solutions and compounds of transition elements alter the nature of the concrete strength formation, namely increase the rate of strength formation of reactive powder concretes in the initial period due to micellar catalysis of cement hydration and maintain increased compressive strength at later stages of hardening through the impact of compounds of transition elements, formation of minerals, containing high amount of chemically-bound water. It is proved that micellar catalysis can be used to control the processes of cement hardening and strength formation of artificial stone, produced in the cement hydration, thereby reducing the time to achieve the concrete design strength and increasing the absolute value of compressive strength of such concretes at 28 days using compounds of transition elements.